2015
DOI: 10.1007/s12630-015-0505-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal quantitative sensory testing to assess the sensory effects of three local anesthetic solutions in a randomized trial of interscalene blockade for shoulder surgery

Abstract: Thermal quantitative sensory testing to assess the sensory effects of three local anesthetic solutions in a randomized trial of interscalene blockade for shoulder surgery Les tests sensoriels quantitatifs thermiques utilisés pour évaluer les effets sensoriels de trois solutions d'anesthésiques locaux dans une étude randomisée de blocs interscaléniques pour les chirurgies de l'épaule Methods This was a prospective randomized trial in patients scheduled for arthroscopic shoulder surgery under general anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The thermal threshold has been used in previous studies to get a more objective measurement of the analgesic effect [ 24 , 25 ]. In dogs, TT has been reliably measured [ 26 ] to evaluate pain in different conditions [ 27 , 28 , 29 ] and to evaluate the efficacy of analgesics [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal threshold has been used in previous studies to get a more objective measurement of the analgesic effect [ 24 , 25 ]. In dogs, TT has been reliably measured [ 26 ] to evaluate pain in different conditions [ 27 , 28 , 29 ] and to evaluate the efficacy of analgesics [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, TT has been reliably measured [ 26 ] to evaluate pain in different conditions [ 27 , 28 , 29 ] and to evaluate the efficacy of analgesics [ 30 ]. Thermal threshold testing has been used in human anaesthesia to assess the effect of loco-regional anaesthesia techniques and the differences among several drugs [ 25 ]. Our study showed a significantly increased thermal threshold in all dermatomes (T 10 , T 13 , L3 ) on both sides of the skin of the abdominal wall when it was assessed 30 min after the recovery, compared with the basal values before the block.…”
Section: Discussionmentioning
confidence: 99%
“…37 Limitations of this study include the generalisability of results from a small number of volunteers to the large, diverse group undergoing surgery. While pinprick sensation is commonly used to evaluate time-to-event regional anaesthesia outcomes and there is growing experience for utilisation of QST in regional anaesthesia studies, 20,38 it is unclear exactly how these modalities correlate to post-surgical pain. Another limitation was that some volunteers left before complete resolution of QST modalities, which required forward extrapolation for AUC analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Four QST modalities were assessed: cold detection threshold (CDT), warm detection threshold (WDT), cold pain threshold (CPT), and heat pain threshold (HPT). 20 A standard Peltier thermode was applied over the anaesthetised area of the blocked hand at a starting temperature of 32 C. Thermode temperature was decreased or increased by 1 C s À1 . Volunteers were asked to signal CDT, WDT, CPT, and HPT by pressing a handset button with the contralateral hand.…”
Section: Neurological Assessmentsmentioning
confidence: 99%
“…Although perforation of the epineurium and subsequent injection does not always result in neurological damage , we should remain vigilant and use all tools at our disposal to avoid intraneural injection . Since we are performing the tangential approach routinely in clinical practice, we have no concerns about the effectiveness of the block .…”
Section: Discussionmentioning
confidence: 99%